TINJAUAN HUKUM ISLAM TERHADAP NIKAH FASID DAN DAMPAKNYA (Studi Terhadap Putusan Hakim di Pengadilan Agama Bengkulu - Meiryana, Feity (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
The purpose of the research  is to know the judge’s consideration, the impact of the judge’s decision and the review of Islamic law against  the marriage  of the fakid in the Religious Court of Bengkulu.  Research  type is normative. The research approach is the  case  approach. Data  collection  techniques used  are  literature  techniques from primary  legal materials  and secondary legal materials.  The analysis used  is qualitative  analysis. The result of the research  is that the judge in deciding  the case of marriage  cancellation  has been  in accordance with the Laws Regulation,  because the judge in this case is guided  by the Compilation of Islamic Law and Positive Law. In addition, the impact of the decision of the cancellation  of marriage  is; since the issuance  of the Decision of the Religious Courts that the marital relationship is abolished and  is considered never to carry out the contract of marriage, while the child who has been  born to the marriage  remains  guardian to his father and for the needs  of his life is still the responsibility  of his parents, especially the father. The inheritance of the cancellation  of the marriage  remains joint property.  While fasid marriage  in view of Islamic law is a marriage  that must be canceled because of the terms or pillars of marriage  is not met and violate the rules set by sharia law